2022
DOI: 10.3390/ijerph20010073
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Designed to Support Physical Activity and Disease Prevention for Working from Home: A Scoping Review

Abstract: Working from home (WfH) has public health implications including changes to physical activity (PA) and sedentary behavior (SB). We reviewed published and grey literature for interventions designed to support PA or reduce SB in WfH contexts. From 1355 published and grey literature documents since 2010, we screened 136 eligible documents and extracted ten intervention studies. Interventions designed specifically for WfH were limited and included structured exercise programs, infrastructure (e.g., sit-stand works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A recent scoping review concluded that new evidence is needed to understand how these prepandemic workplace interventions can be translocated to the remote or hybrid work environment. 34 Several approaches have been offered for increasing PA and reducing sedentary behavior in these new work arrangements, including active workstations (eg, sit-stand desks), employee incentive programs (eg, gym memberships), activity trackers, screen time control devices, and computer-based prompts for movement. 29,34 Active People, Healthy Nation, SM an initiative by the Centers for Disease Control and Prevention, promotes evidence-based strategies to increase PA across the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent scoping review concluded that new evidence is needed to understand how these prepandemic workplace interventions can be translocated to the remote or hybrid work environment. 34 Several approaches have been offered for increasing PA and reducing sedentary behavior in these new work arrangements, including active workstations (eg, sit-stand desks), employee incentive programs (eg, gym memberships), activity trackers, screen time control devices, and computer-based prompts for movement. 29,34 Active People, Healthy Nation, SM an initiative by the Centers for Disease Control and Prevention, promotes evidence-based strategies to increase PA across the population.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several approaches have been offered for increasing PA and reducing sedentary behavior in these new work arrangements, including active workstations (eg, sit-stand desks), employee incentive programs (eg, gym memberships), activity trackers, screen time control devices, and computer-based prompts for movement. 29,34 Active People, Healthy Nation, SM an initiative by the Centers for Disease Control and Prevention, promotes evidence-based strategies to increase PA across the population. Some of these strategies, such as community design interventions and social support, 35 could be used to support the PA of teleworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation